Brain Gym Associated With Fine Motor Development in Intellectual Disability: Latihan Otak Berkaitan dengan Perkembangan Motorik Halus pada Disabilitas Intelektual - Ulfa Unzilatur Rohmah; Nurfi Laili (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Children with intellectual disabilities experience developmental delays, including limitations in fine motor abilities required for daily tasks such as writing, coloring, cutting, and pasting. Specific Background: Fine motor skills depend on coordinated small muscle movements, and structured learning interventions are needed to support development in special education contexts. Brain gym, consisting of coordinated body movements, is used to stimulate brain coordination and support learning activities. Knowledge Gap: Empirical evidence using single-subject experimental designs examining brain gym application for fine motor development in children with intellectual disabilities remains limited. Aims: This study aimed to determine whether the brain gym method is associated with improvements in fine motor skills among children with intellectual disabilities at SLB Aisyiyah Tulangan Sidoarjo. Results: Using a single subject research A–B–A design and structured observation, fine motor performance in writing, pasting, coloring, and cutting increased from a total pretest score of 8 to a posttest score of 13. Paired sample t-test analysis showed a significant difference between measurements (t = 5.000; p = 0.015 < 0.05). Novelty: The study documents measurable changes in multiple fine motor indicators through a single-subject experimental framework. Implications: The findings support movement-based learning activities as complementary practices in special education programs to support fine motor skill development. Highlights: Observational Scoring Increased Across Writing, Pasting, Coloring, and Cutting Activities After Treatment. Statistical Testing Confirmed Significant Differences Between Baseline and Post-Intervention Measurements. Structured Movement Sessions Demonstrated Measurable Progress Within an a–B–a Experimental Design. Keywords: Brain Gym, Fine Motor Skills, Intellectual Disability, Single Subject Research, Special Education